2018
DOI: 10.3389/fvets.2018.00157
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Osteometric Analysis of Mandibular Symmetry and Morphological Consistency in Cats

Abstract: Objectives: The aim of this study was to describe a number of anatomical reference points which can be used to measure mandibular morphology and assess the degree of mandibular symmetry in a group of normal cats. Comparisons were then made between cats to evaluate correlations between morphological measurements and degree of inter-cat variation. This will provide data valuable evaluating and developing techniques for caudal mandibular fracture repair.Methods: Twenty-seven mixed breed cats (26 Domestic Shorthai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Southerden et al [ 16 ] reported that there is a low level of asymmetry between contralateral mandibles in cats, allowing the use of a mirror image of an intact mandible for planning and evaluating the accuracy of fixation of a contralateral mandible. The most consistent measurement among 27 specimens was the lateral ramus inclination angle.…”
Section: Mandibular Fracturesmentioning
confidence: 99%
See 4 more Smart Citations
“…Southerden et al [ 16 ] reported that there is a low level of asymmetry between contralateral mandibles in cats, allowing the use of a mirror image of an intact mandible for planning and evaluating the accuracy of fixation of a contralateral mandible. The most consistent measurement among 27 specimens was the lateral ramus inclination angle.…”
Section: Mandibular Fracturesmentioning
confidence: 99%
“…The most consistent measurement among 27 specimens was the lateral ramus inclination angle. However, the least consistent measurements were ramus height and jaw width at the mental foramen [ 16 ]. This type of study may facilitate the development of standardised pre-contoured locking plates for cat mandible repair.…”
Section: Mandibular Fracturesmentioning
confidence: 99%
See 3 more Smart Citations